The Impact of the Federal Budget - Smithies, A. (The Review of Economics and Statistics, 1947)
shall escape a serious wage-price spiral, leading to collapse, within the coming year and a half. In effect, we believe, this is to assume that throughout this period union wage demands are kept within very moderate limits. No doubt it is incorrect to say that the inflationary pressure on wage levels observable at full employment results exclusively from union behavior; we know from the experience of previous booms that competition will generate it in markets, and the evidence of the past fifteen months suggests that this will be true even under price ceilings. But powerful unions enhance the pressure immeasurably in at least two ways: ( i ) they tend to force increases much larger than those which would take place under competitive conditions in factor and product markets; and (2) they intensify the speed and magnitude of any reaction of wages to a rise in prices, when the latter are free to rise. With price controls rapidly going by the boards, they will now be able to move along both avenues. At the present writing (November, I946), among the agents making for rapid short-term inflation they seem to be the most important as they are the least controllable. If they run wild, the inevitable collapse might create a need for a strong reflationary policy.